ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGAMBILAN OBAT PESERTA PROGRAM RUJUK BALIK DI BANDAR LAMPUNG - Setyaningrum, Ndaru; Pramantara, I Dewa Putu (Indonesian Research Gateway)
ABSTRACT : Program (Program Rujuk Balik = PRB) through a health care program for the participants of the National Health Insurance with chronic diseases. Barriers to success of therapeutic treatment for patients with chronic diseases is non-adherence related to the patient's treatment regimen. Taking medication adherence for patients with chronic illness is the first adherence can be assessed on how a person decides to get medicines for themselves. Analyzing factors affecting medication adherence taking participants PRB is important, cause non-adherence adverse effects appear in the treatment. Participants adherence taking the drug on a PRB can be obtained from the data prescription claims to calculate the medication possession ratio (MPR), which MPR ≥ 80% declared adherence. Data obtained from prescription claim by participants PRB for September 2015 until December 2015 in Bandar Lampung. Sample case study 82 people with diabetes. The calculation result MPR explains that 62.2% of respondents declared adherence taking medication, while 37.8% of respondents declared non-adherence. The results of the logistic regression analysis, stating that there are influences together of factors respondents' knowledge, respondents belief, attitudes of personnel pharmacy services, pharmacy facilities, cost, availability of medication PRB, family support, and accessibility affect to respondent adherence of taking medication. However, factors that significantly influence medication adherence refer the decision back is knowledge of respondents with sig = 0,028 (sig <0.05), belief of respondents with sig = 0,003 (sig <0.05), and accessibility sig = 0,044 (sig < 0.05) significantly affect to adherence of taking medication.